The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s40519-017-0440-7
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the mechanisms and personality traits underlying food addiction among individuals with severe obesity awaiting bariatric surgery

Abstract: Level V, descriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 44 publications
3
19
0
1
Order By: Relevance
“…Other current findings contradict the assumption that the patients might have under‐report psychopathology. In accordance with our hypothesis, the prevalence of probable eating, anxiety, and major depressive disorders in the present sample was as high as expected based on literature (Baldofski et al, ; Brunault et al, ; Brunault et al, ; Ivezaj et al, ; Koball et al, ; Meule et al, ; Meule et al, ; Miller‐Matero et al, ; Ouellette et al, ). The current results further resemble findings from previous studies in bariatric surgery patients that indicate that those with FA are more likely than those without FA to exhibit eating disorder and anxiety and depressive disorder symptoms (Brunault et al, ; Koball et al, ; Meule et al, ; Miller‐Matero et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Other current findings contradict the assumption that the patients might have under‐report psychopathology. In accordance with our hypothesis, the prevalence of probable eating, anxiety, and major depressive disorders in the present sample was as high as expected based on literature (Baldofski et al, ; Brunault et al, ; Brunault et al, ; Ivezaj et al, ; Koball et al, ; Meule et al, ; Meule et al, ; Miller‐Matero et al, ; Ouellette et al, ). The current results further resemble findings from previous studies in bariatric surgery patients that indicate that those with FA are more likely than those without FA to exhibit eating disorder and anxiety and depressive disorder symptoms (Brunault et al, ; Koball et al, ; Meule et al, ; Miller‐Matero et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…It is well known that individuals with obesity seeking bariatric surgery are often suffering from FA (for review, see Ivezaj, Wiedemann, & Grilo, 2017); however, the reported proportions of YFAS based FA diagnoses in preoperative samples showed wide variation, ranging from 6.7% (Chao et al, 2017) to 58% (Sevincer, Konuk, Bozkurt, & Coskun, 2016). There is also evidence that bariatric surgery candidates with FA are more likely to exhibit symptoms of comorbid mental disorders than those without FA, including eating, anxiety, and depressive disorders (Baldofski et al, 2015;Brunault et al, 2016;Brunault et al, 2018;Ivezaj et al, 2017;Koball et al, 2016;Meule et al, 2017;Meule, Heckel, Jurowich, Vögele, & Kübler, 2014;Miller-Matero et al, 2014;Ouellette et al, 2017).…”
mentioning
confidence: 99%
“…Several studies also demonstrated the close association between FA, as assessed by the YFAS 2.0, and psychiatric or psychological factors usually associated with SRAD [see Burrows et al (23) and Penzenstadler et al (24) for recent reviews]: impulsivity (25), especially attentional and motor impulsivity (26), higher levels of psychopathology (27)(28)(29), poorer emotion regulation skills (30), emotional eating (31), and psychiatric disorders such as mood and anxiety disorders (30,32), eating disorders (33)(34)(35), eating disorder severity (30), and higher suicidality (32) and non-suicidal self-injury (33).…”
Section: Introductionmentioning
confidence: 99%
“…Food addiction based on YFAS scale, is rare in healthy eating/weight participants (2–12%; Gearhardt, Grilo, et al, ; Aloi et al, ; Meule et al, ; Schulte & Gearhardt, ), but is more prevalent in subjects with obesity (ranging from 18 to 24%) and even higher in patients with ED, particularly BED and BN (ranging from 70% to 95%, respectively) (Gearhardt et al, ; Granero et al, ; Hilker et al, ). When considering gender, FA seems to be more prevalent in females than males, in obesity, healthy population and behavioral addictions (Jiménez‐Murcia et al, ; Ouellette et al, ; Pursey et al, ), but not in ED (Gearhardt et al, ; Granero et al, ), where FA seems to be similarly prevalent as well in females as in males. Considering the literature, published so far, FA is frequently associated with higher ED severity and more general psychopathology (Granero et al, ; Granero et al, ; Piccinni, Marazziti, Cargioli, Mauri, & Stallone, ), but also with more dysfunctional personality traits, namely negative urgency and impulsivity (Wolz et al, , ; Ouellette et al, ).…”
mentioning
confidence: 99%